Communication barrier among mobility students at a Malaysian public university - Roslan, Nur Maisarah (2016)
Mobility program has been carried out throughout the universities from all over the world. This is due to the fact that the mobility program will ensure the link and communication between universities. The International Division (ID) at Universiti Putra Malaysia (UPM) has been dealing with foreign learners from all over the world. Communication in English therefore it is vital for these students to ensure the smooth running of their housing and visa application, as well as for the course registration. Since, English language is not the first language for most of the mobility students as well as the locals in Malaysia, they tend to face problem in getting their message across during conversation. Hence, the objectives of the study are to identify the types of communication barriers according to Stubb’s (1983) theory and to discuss the factors affecting the communication barrier among mobility students at ID, UPM. The respondents of the study consist of 60 male and female subjects from 29 universities all around the world, aged between 20 to 31 years old. Data collection took place at ID, UPM. The current study used interviews to observe the students opinion on their mobility program at UPM. The subjects were interviewed individually and the interview sessions were video-taped for the purpose of the study. The data from the interviews will be analysed based on Stubbs (1983) theory. The overall results showed that communication barriers exist among mobility students at UPM. Although, the mobility students were able to speak in the English language, but it can be said that the language spoken was difficult to be understood. The results of the study revealed that all the subjects have used the approaches proposed by Stubbs (1983) to overcome their communication problems namely; predictability, phonotactics, grammatically, intuition, analogies and conclusions. The subjects seemed to be comfortable using words and sentences that make sense to them. Equally, all the subjects were also found to have uttered words and sentences which were related to their culture/background, accent and need and faced a lot of problems when communicating due to the influences occurred. It is hoped that this study will contribute in identifying the communication barriers faced by mobility students at ID, UPM and future studies help to overcome the communication barriers among mobility students.